2015
DOI: 10.1080/14786435.2015.1006291
|View full text |Cite
|
Sign up to set email alerts
|

Mild degradation processes in ZnO-based varistors: the role of Zn vacancies

Abstract: The effects of a degradation process on the structural and electrical properties of ZnO-based varistors induced by the application of dc bias voltage were analysed. Capacitance and resistance measurements were carried out to electrically characterize the polycrystalline semiconductor before and after different degrees of mild degradation. Vacancies' changes in the varistors were studied with positron annihilation lifetime spectroscopy. Variations on the potential barrier height and effective doping concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Furthermore, it has been reported that mild degradation after applying an electric field stress leads to a decrease in the effective doping concentration at the grains and accordingly to an increase in the resistance of grain boundaries [6]. This increase clearly explains the increase in Vv.…”
Section: Physical Bases Of Degradation Processes and Mathematical Modsupporting
confidence: 49%
See 3 more Smart Citations
“…Furthermore, it has been reported that mild degradation after applying an electric field stress leads to a decrease in the effective doping concentration at the grains and accordingly to an increase in the resistance of grain boundaries [6]. This increase clearly explains the increase in Vv.…”
Section: Physical Bases Of Degradation Processes and Mathematical Modsupporting
confidence: 49%
“…Interface trapping of electrons is generally considered to be the mechanism that gives rise to double Schottky barriers at grain boundaries [26]. Furthermore, it has been reported that mild degradation after applying an electric field stress leads to a decrease in the effective doping concentration at the grains and accordingly to an increase in the resistance of grain boundaries [6]. This increase clearly explains the increase in Vv.…”
Section: Physical Bases Of Degradation Processes and Mathematical Modelingmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, PALS has demonstrated to be a powerful tool to investigate the presence of vacancy-like defects in semiconductors 15,16 . This technique has also been successfully used to obtain information on the defect structure of monocrystalline and polycrystalline semiconductor metal oxides [17][18][19][20][21][22][23][24] . In fact, vacancies in neutral or negative charge states act as efficient positron traps due to the reduced repulsion of positive ions, while positive vacancies do not trap positrons.…”
Section: Introductionmentioning
confidence: 99%